CONTESTATION OF THEOLOGICAL THOUGHT DURING THE COVID 19 PANDEMIC (INDONESIAN CONTEXT) - Kasriadi Kasriadi; Barsihannor Barsihannor; Indo Santalia (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
The involvement in theological thought (kalam) during the Covid-19 pandemic in Indonesia can be summarized into three groups. First, fatalism is the understanding of a society that believes that everything in this world is the totality of destiny and is the decree of Allah SWT. The second understanding is free will, believing in a person's freedom to choose between different plans and actions rather than waiting for fate to befall him. The third one is a central axis theology. Religious moderation can be understood as a view, attitude, or action that always takes the middle, fair, and non-extreme path in religion. Religious moderation should be understood as a balanced religious attitude between the practice of one's own religion (exclusive) and respect for the religious practices of other religions (inclusive).